Quantitative and Qualitative Pathogenetic Indices for Review of Data Derived from Homeopathic Pathogenetic Trials - Shah, Rajesh (Homeopathy, 2018)
Introduction Analysis of data derived from homeopathic pathogenetic trials (HPTs, homeopathic drug provings) has been a challenge. Most parts of the homeopathic pharmacopeia were sourced from Hahnemann's Materia Medica Pura (1825–1833), TF Allen's Encyclopedia (1874) and Constantine Hering's Materia Medica (1879–1891), well before randomised controlled trials were in use. As a result, such studies and their outcomes harbour a large risk of inclusion of unreliable symptoms.Aims and Objective The main purpose of this article is to introduce Quantitative and Qualitative Pathogenetic Indices to improve the method of analysis of symptoms.Materials and Methods The data from HPTs for human immunodeficiency virus nosode, hepatitis C nosode, capsaicin alkaloids (capsaicin and dihydrocapsaicin) and hydroquinone (HQ) were extracted and analysed in terms of novel Qualitative and Quantitative Pathogenetic Indices. Taken into the consideration were the qualitative aspect of a symptom (i.e. its intensity), and the quantitative aspect by calculating the number of symptoms per volunteer per day. The pathogenetic effects and data evaluation indices were calculated for each HPT. A comparison was made of symptoms of verum versus placebo provers in terms of their quantity and quality.Results Four HPTs involving 81 volunteers (56 on verum and 25 on placebo) generated 555 symptoms or pathogenetic effects (excluding run-in phase symptoms), of which 448 (81%) were reported by volunteers who were in the verum arm, and 107 (19%) were reported by volunteers on placebo. The overall mean incidence of pathogenetic effects for the four HPTs was thus 8 per verum prover and 4.28 per placebo prover. The corresponding mean Quantitative Pathogenetic Index was 0.23 symptoms per volunteer per day for the verum arm and 0.12 symptoms per volunteer per day for the placebo arm. The overall mean incidence of pathogenetic effects in the run-in phase was less. The overall mean Qualitative Pathogenetic Index (number of symptoms, of a given intensity, per volunteer per day) for the verum arm was 0.09 versus 0.05 for the placebo arm.Conclusion The symptoms exhibited by volunteers in the verum arm were more numerous and more intense than those in the placebo arm. An innovative and logical method of reporting of symptoms and analysis has been introduced by the use of these pathogenetic indices, which can be used in future as measurement tools for analysis of data from HPTs.
Keywords: homeopathic pathogenetic trial; drug proving; symptoms; qualitative pathogenetic index; quantitative pathogenetic index; homeopathy